Detection of Phytoplankton Blooms in the Upper Gulf of Thailand Using Sentinel-3A OLCI Imagery - Teerawat Suwanlertcharoen; Siriluk Prukpitikul (Environment and Natural Resources Journal, 2017)
This study aims to use Sentinel-3A Ocean and Land Color Instrument (OLCI) imagery for detecting phytoplankton blooms in the Upper Gulf of Thailand by using the Maximum Chlorophyll Index (MCI). The results showed that the MCI was able to detect phytoplankton blooms in the study area. The areas with intense phytoplankton blooms showed high MCI values. The radiance spectrum (with a reflectance peak at wavelength 708.75 nm) and the difference between baseline wavelengths 708.75 nm and 681.25 nm were quite high. High MCI values corresponded well with locations of phytoplankton blooms seen on RGB False-Color Composite images. Thus, time series analysis of MCIs obtained from Sentinel-3A OLCI images could be used in detecting, tracking, and delineating phytoplankton blooms.